Experimental studies of the strength of masonry under axial and local compression - Pents, Maryna; Dovzhenko, Oksana (Academic journal Industrial Machine Building Civil Engineering, 2025)
Masonry is one of the traditional building materials that remains highly relevant in modern civil and industrial construction. Determining its strength characteristics, especially under compressive loads, remains an important scientific and technical task, since such forces prevail in load-bearing walls, columns, and other structural elements of masonry. The compressive strength of masonry is affected by numerous factors, including the strength and geometric properties of the units, their shape accuracy, the presence of voids, the mortar strength, the deformation characteristics of hardened mortar, the workability of the mortar mix, the bond strength between mortar and masonry units, the degree of joint filling, the bonding pattern, and the overall quality of workmanship. When determining the strength of masonry under local compression, the nature of the sample’s destruction is taken into account, on the basis of which a corresponding kinematic scheme is developed that determines the main parameters that affect the strength of the masonry. One of the key issues is the lack of a unified approach to determining the geometric parameters of the samples used for testing. The objective of this study is: 1. to develop scientifically based recommendations for the optimal shape and size of standard samples that allow the most reliable assessment of the axial compressive strength of masonry based on test results; 2. to consider the case of local compression of walls by stamps located near the end face with a width less than the wall thickness.